Oligocene-Miocene lacustrine rudite-dominated alluvial-fan delta, southwest Montana, U.S.A. - Flores, R.M.; M’gonigle, J.W. (Cuadernos de Geología Ibérica, 1991)
Facies continuum and facies profiles from outcrops aud drilí cores in die Tertiar>’ Medicine Lodge beds were analyzed in the Medicine Lodge and Horse Prairie basins in Southwest Montana, U.S.A. These betAs consist of interbedded conglomerates. sandstones, siltstones, mudstones, limestones, carbonaceous sitales, antA coals that malce up coarsening- and fining-upward megasequences. Tite study indicates titat die Medicine Lodge beds were deposited in freshwater lake alluvial-fan delta antA sitort-headed stream delta environments. The lake, whicit probabí>’ occurred in an asymmetrical protobasin formed during Laramide deformation and ancestral to tite Medicine antA Horse Prairie basins, was initialí>’ infilled by coal-forming, short-headed stream deltas antA littoral lacustrine carbonate platfonns alqng its steeply dipping margin. Ihis early stage of infilling was characterized by rapid basin subsidence, witich was accompanied by lake expansion, antA by subdued provenance tectonism developed west-soudiwest of tite protobasin. Ibe late stage of lake infilhing continued along tite steeply dipping margin of the protobasin where east-northeast flowing alluvial-fan delta complex formed an aggrading, subaerial alluvial fan antA a prograding, subaqueous delta front. Tite alluvialfan delta complex was bounded tú tite south by a lacustrine coastal plain that was drainedby coal-forming, short-headed streams deltas antA tú the immediate nortit by lacustrine littoral carbonate platforms that supported stromatolite Cuadernos de Geología Ibérica N.0 15, 241-278. Madrid, 1991. Edit. Universidad Complutense. R. Al. Flores & J. W. M’Gonigle 242 bioitenns. Titis stage of lake-basin infilling was marked by intense provenance uplifts and was accompanied by moderate basin subsidence antA local lake expansion with marked lake-level fluctuations. Climate did not significantly influence fluctuations of the lake level since tite lake remained fresitwater and open throughout infilling. However, microclimate (e.g., ram sitadows) may have controlled coal distribution in the Medicine Lodge basin part of tite protobasin. Humid-temperate climate is indicated by common presence of debris flows on the alluvial fan, which were triggered it>’ intense rainfalí. Titus, tite lake protobasin is a microcosm of clastic, carbonate and organic environments, itydrodynamics, provenance tectonism, climate, and basin subsidence titat greatí>’ influenced facies variations.